Effect of Captopril on Brain Oxidative Damage in Pentylenetetrazole-Induced Seizures in Mice - Fereshteh Asgharzadeh; Mahmoud Hosseini; Rahimeh Bargi; Mohammad Soukhtanloo; Farimah Beheshti; Zohreh Mohammady; Akbar Anaeigoudari (Tabriz University of Medical Sciences, 2019)
Background: Frequent seizure is followed by overproduction of free radicals and brain oxidative stress. Renin angiotensin system (RAS) has some effects on central nervous system. We designed this research to challenge the effect of captopril as an angiotensin converting enzyme (ACE) inhibitor against brain oxidative stress in pentylenetetrazole (PTZ) -induced seizures in mice. Methods: The groups were including (1) Control (saline); (2) PTZ (100 mg/kg, i.p.), (3-5) PTZ- captopril (Capto) that received three doses of Capto 10, 50 and 100 mg/kg 30 min before PTZ injection. Latency time in the onset minimal clonic seizures (MCS) and generalized tonic-clonic seizures (GTCS) were recorded. The level of malondialdehyde (MDA) and total thiol, as well as superoxide dismutase (SOD) and catalase (CAT) activity in the hippocampus and cortex were measured. Results: All doses of captopril postponed the onset of MCS and GTCS. Accumulation of MDA in the brain tissues of PTZ group was higher than control group, while total thiol content and CAT activity were lower. Pretreatment with captopril (100 mg/kg) diminished MDA concentration compared with PTZ group. Captopril (50 and 100 mg/kg) also increased the level of total thiol groups versus PTZ group. Captopril injection (50 and 100 mg/kg) elevated the activity of SOD and CAT in the brain tissues. In addition captopril administration diminished mortality rate caused by PTZ. Conclusion: Findings demonstrated that convulsions caused by PTZ were followed by oxidative stress status in the brain tissues. Pretreatment with captopril attenuated the effect of PTZ on brain tissue oxidative damage.